Pengaruh Kompensasi Terhadap Kinerja Karyawan pada PT. Cepart Indonesia Cabang Pekanbaru - Indri, lasmini; yapentra, arhipen (Sekolah Tinggi Ilmu Ekonomi Riau, 2024)
The purpose of this study was to determine the effect of compensation on employee performance at PT CEPART Indonesia, Pekanbaru Branch, located at Jl. Garuda Sakti Km. 3, Pergudangan Angkasa II. The study population consisted of 34 employees. Data analysis showed a t-value for the compensation variable of 4.646 with a significance level of 0.000. This indicates that compensation significantly influences employee performance. The correlation (R) value of 0.403 indicates that compensation has a 40.30% effect on employee performance. Thus, it can be concluded that compensation significantly influences employee performance at PT CEPART Pekanbaru Branch.